Contracts Applied in Indonesia Sharia Interbank Money Market (PUAS); An Analysis from Comparative Fiqh Views - Abdurrubi, Salman; Sulthon Aziz, Muhammad (Tribakti: Jurnal Pemikiran Keislaman, 2023)
Bank Indonesia Regulation (22/9/PBI/2020) administers that Sharia Interbank Money Market (PUAS) is based on particular instruments which are SIMA (Mudarabah Interbank Investment Certificate), SiKA (Commodity Murabahah Investment Certificate) and SiPA (Wakalah bil-Istismar or Investment Agency Certificate). Despite the existing fatwas (DSN-MUI 37/X/2002, 38/X/2002, and 78/IX/2010) rule the principles within PUAS in Indonesia, are straightforward and concise. Hence, it is crucial to develop extended fiqh deliberation on the regulation as it can further develop and evaluate the current practice. The research aims mainly at achieving clarity from comparative fiqh views on the practice of conventional and Islamic banks mixed funds within the PUAS. Particularly, it will examine whether the existing Islamic contracts offered within PUAS encounter potential fiqh issues. This study applies a qualitative approach using the content analysis method namely a comparison of jurist views and legal maxims. It summarised: (i) there is no fiqh issue in the use of excess liquidity from conventional banks to be invested in sharia banks with the rationale of Quran (2:274) and Legal Maxim of â€œit is absolved in dependent events and not so for independent onesâ€, (ii) the subject-matter of each contract within PUAS, capital and work in Mudharabah, price and goods in commodity Murabaha, and trusted funds in wakalah bil-istismar, has no potential fiqh issue with regarding the mandatory condition of subject-matter that should be sharia-compliant. (iii) However, although utilizing comingled wealth is permissible, nonetheless it stands under detestation. As such, the commodity murabahah contract (SiKA) has fewer fiqh issues because it dissociates sharia banks in PUAS to expose directly to excess liquidity from conventional banks